2021
DOI: 10.20892/j.issn.2095-3941.2020.0566
|View full text |Cite
|
Sign up to set email alerts
|

Raltitrexed as a synergistic hyperthermia chemotherapy drug screened in patient-derived colorectal cancer organoids

Abstract: Objective: Organoids have recently been used as in vitro models to screen chemotherapy drugs in combination with hyperthermia treatment in colorectal cancer. Our research aimed to establish a library of patient-derived colorectal cancer organoids to evaluate synergism between chemotherapy drugs and hyperthermia; validate an index of the hyperthermia chemotherapy sensitization enhancement ratio (HCSER) to identify the chemotherapeutics most enhanced by hyperthermia; and recommend chemotherapy drugs for hyperthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It was of paramount importance that PDOs adequately represented the disparate morphologic and histologic characteristics of different CRC subtypes. The PDOs from different patients showed diversity in growth rate and morphology, and it was essential that PDOs sufficiently represented the diverse histologic features of different cancer subtypes (Figure ). To compare these features of CRC organoids and original CRC tissues, we performed H&E staining and immunohistochemical (IHC) analysis (Figure A).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It was of paramount importance that PDOs adequately represented the disparate morphologic and histologic characteristics of different CRC subtypes. The PDOs from different patients showed diversity in growth rate and morphology, and it was essential that PDOs sufficiently represented the diverse histologic features of different cancer subtypes (Figure ). To compare these features of CRC organoids and original CRC tissues, we performed H&E staining and immunohistochemical (IHC) analysis (Figure A).…”
Section: Results and Discussionmentioning
confidence: 99%
“… [ 65 ] CRC Raltitrexed, OXA, MMC, GEM, 5-FU, Lobaplatin, Abraxane CCK-8 Raltitrexed has the most significant hyperthermia synergism among the common hyperthermic intraperitoneal chemotherapy drugs in CRC PDOs. [ 66 ] mCRC 5-FU, OXA, CPT-11 CTG The drug tests based on mCRC PDOs successfully predict the drug response to CPT-11 but fail to predict drug response to 5-FU plus OXA. [ 31 ] mCRC 5-FU, OXA, CPT-11, SN-38 CTG mCRC PDOs show sensitivities to 5-FU, SN-38, the same as drug responses in clinic.…”
Section: Gic Pdos As An Advantageous Preclinical Model For Radiothera...mentioning
confidence: 99%
“…PDOs could also be applied to detect the combined anti-cancer effect between chemotherapy and other treatment methods. Zeng et al firstly established a library of CRC PDOs from 22 patients to evaluate the combined anti-cancer effect between hyperthermia and chemotherapy drugs [ 66 ]. They found that raltitrexed had the most significant hyperthermia synergism among the 7 common hyperthermic intraperitoneal chemotherapy drugs in CRC PDOs [ 66 ].…”
Section: Gic Pdos As An Advantageous Preclinical Model For Radiothera...mentioning
confidence: 99%
“…Since Sato et al 6 first generated crypt-villus organoids from Lgr5(+) stem cells, organoid technology has become a promising tool in disease modeling. Many PDOs have been successfully constructed from breast cancer (BC), ovarian cancer (OC) 7 9 , lung cancer 10 , gastric cancer (GC) 11 , prostate cancer 12 , bladder cancer (BLC) 13 , liver cancer 14 , esophageal adenocarcinoma (EAC) 15 , pancreatic cancer (PC) 16 , neuroblastoma tumors, glioblastomas 17 , and colorectal cancer (CRC) 18 , 19 . Similarly, in the past 10 years, tumor organoids have become commonly used tools in oncology research ( Table 1 and Figure 1 ), including studies on cancer initiation and progression, preclinical models 20 , explorative and personalized therapies 21 , and drug screening 22 .…”
Section: Introductionmentioning
confidence: 99%